2018
DOI: 10.1039/c8ta01772g
|View full text |Cite
|
Sign up to set email alerts
|

Entropy-stabilized metal oxide solid solutions as CO oxidation catalysts with high-temperature stability

Abstract: This work reports a new strategy toward the design of a new class of supported catalysts with intrinsic high-temperature stabilities through entropy maximization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
165
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 235 publications
(170 citation statements)
references
References 24 publications
2
165
0
3
Order By: Relevance
“…It was demonstrated that Pt(II) can be readily doped into the rock-salt structure of CuO-ZnO-CoO-NiO-MgO. [6] The Pt(II) species (up to 5wt%)c an be readily doped into the lattice without observation of an XRD pattern correspondingt o Pt or PtO NPs under high-temperature conditions. The advantage of this class of SACs involving Pt species was clearly demonstrated with the CO oxidation reactiona saprobe reaction ( Figure 2).…”
Section: Non-alloy Hemsmentioning
confidence: 99%
“…It was demonstrated that Pt(II) can be readily doped into the rock-salt structure of CuO-ZnO-CoO-NiO-MgO. [6] The Pt(II) species (up to 5wt%)c an be readily doped into the lattice without observation of an XRD pattern correspondingt o Pt or PtO NPs under high-temperature conditions. The advantage of this class of SACs involving Pt species was clearly demonstrated with the CO oxidation reactiona saprobe reaction ( Figure 2).…”
Section: Non-alloy Hemsmentioning
confidence: 99%
“…[1][2][3][4][5][6] HEMs are based on the premise of incorporatingm ultiple components (usually five or more) into as ingle crystal phase to attain unique combination of properties that are otherwise unattainable in conventional solid solutions. [10,12,13] Although conventional perovskites with high-surface area have been synthesized previously, [14,15] high-entropy perovskites with high surfacearea have not been reported previously to the best of our knowledge.Perovskites are an important class of materials that exhibit a wide range of functionality,m aking them desirable for use in different areas of application including heterogenous catalysis. Examples include high-entropy metal dibor-ides, [4] high-entropy nitrides, [8,9] and high-entropy metal oxides (HEMOs).…”
mentioning
confidence: 97%
“…Ta king advantage of the acoustic cavitation phenomenon in theu ltrasonication process, BaSr(ZrHf-Ti)O 3 ,B aSrBi(ZrHfTiFe)O 3 and Ru/BaSrBi(ZrHfTiFe)O 3 nanoparticles were crystallized as single-phase perovskite structures through ultrasonication exposure withoutc alcination. [10] More recently,J iang et al extended the HEMO study to include perovskite-type oxides with six and seven metallice lements. [1][2][3][4][5][6] HEMs are based on the premise of incorporatingm ultiple components (usually five or more) into as ingle crystal phase to attain unique combination of properties that are otherwise unattainable in conventional solid solutions.…”
mentioning
confidence: 99%
See 2 more Smart Citations